Saturday

April 19, 2014

April 19, 2014

Posted by **Felix** on Wednesday, September 5, 2012 at 4:06pm.

- Physics -
**Steve**, Wednesday, September 5, 2012 at 4:21pmjust multiply exponents when raising an expression to a power:

(5x^-3)^2 = 5^2 (x^-3)^2

= 25 x^(-3*2)

= 25x^-6

recall that (x^-3)^2 is just x^-3 * x^-3 = x^(-3 + -3) = x^-6

**Related Questions**

Math - 1.Write the equation 5x+y-2=0 in normal form. 5x+y-2=0 5x+y=2 (add two to...

algebra - Factor by grouping 5x^3-5x^2-x+1 Would it be? (x-1)(5x^2-1) or (5x^2-1...

Math - if f(x) = 2x^2 + 5x, find f(x+h) - f(x) / h and simplify. I started to ...

algebra 3 - which number is a the solution of the equation [5x-2] = 8? a.}6/5 b...

Math - please help - Write an equation for the line that is parallel to the ...

how about his one - -7+ 5x = 10x-2? im not sure I know its -1, but im not sure ...

pre algebra and trigonomerty - 5x+5 +5x+13 5x+9 5x+9

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

Algebra - How can you factor? x^6+y^6 That expression cannot be factored further...

algebra1/McDougal Littell - I need to know how to work this problem and show my ...